2022
DOI: 10.3390/cancers14225684
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Associated ECM Remodeling in Cancer Progression

Abstract: Adipose tissue, an energy storage and endocrine organ, is emerging as an essential player for ECM remodeling. Fibrosis is one of the hallmarks of obese adipose tissue, featuring excessive ECM deposition and enhanced collagen alignment. A variety of ECM components and ECM-related enzymes are produced by adipocytes and myofibroblasts in obese adipose tissue. Data from lineage-tracing models and a single-cell analysis indicate that adipocytes can transform or de-differentiate into myofibroblast/fibroblast-like ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 90 publications
(178 reference statements)
0
8
0
Order By: Relevance
“…The ECM plays a crucial role and contributes to the hallmarks of cancer in tumor progression, metastasis, and response to therapy [ 7 , 8 ]. The ECM can (1) secrete growth factors and cytokines that promote cell proliferation and survival [ 9 ], (2) modulate the expression of genes involved in cell cycle regulation and apoptosis [ 10 ], (3) control the expression of telomerase, an enzyme that extends the telomeres of chromosomes, (4) secrete angiogenic factors that promote the formation of new blood vessels, thereby providing the tumor with the nutrients and oxygen it needs to grow [ 11 ], (5) promote the epithelial-to-mesenchymal transition (EMT), a process by which epithelial cells acquire the ability to migrate and invade other tissues [ 12 ], and (6) temper the immune response by influencing the recruitment and function of immune cells in the TME [ 13 ]. Romero-López and colleagues [ 14 ] tested how the ECM derived from normal and tumor tissues impacted blood vessels and tumor growth using reconstituted ECM.…”
Section: Physiological Relevance Of 3d Cell Cultures To the Ecmmentioning
confidence: 99%
“…The ECM plays a crucial role and contributes to the hallmarks of cancer in tumor progression, metastasis, and response to therapy [ 7 , 8 ]. The ECM can (1) secrete growth factors and cytokines that promote cell proliferation and survival [ 9 ], (2) modulate the expression of genes involved in cell cycle regulation and apoptosis [ 10 ], (3) control the expression of telomerase, an enzyme that extends the telomeres of chromosomes, (4) secrete angiogenic factors that promote the formation of new blood vessels, thereby providing the tumor with the nutrients and oxygen it needs to grow [ 11 ], (5) promote the epithelial-to-mesenchymal transition (EMT), a process by which epithelial cells acquire the ability to migrate and invade other tissues [ 12 ], and (6) temper the immune response by influencing the recruitment and function of immune cells in the TME [ 13 ]. Romero-López and colleagues [ 14 ] tested how the ECM derived from normal and tumor tissues impacted blood vessels and tumor growth using reconstituted ECM.…”
Section: Physiological Relevance Of 3d Cell Cultures To the Ecmmentioning
confidence: 99%
“…Interestingly, a parallel exists between matrix remodelling in obesity and cancer. Many ECM proteins upregulated in AT during obesity are linked with inflammation, the recruiting and conditioning of immune cells and with the promotion of cancer stemness [135][136][137]. ASCs produce a large amount of ECM molecules which can alter TME stiffness, promoting myofibroblast differentiation via mechano-trasduction [133].…”
Section: The Adipose Tissue Stromal Stem Cellsmentioning
confidence: 99%
“…The origin of CAFs is heterogeneous, varies between different tumour histotypes and is critical in determining the degree of CAF malignancy [139]. Recent studies have shown that mature adipocytes, particularly obesity-altered adipocytes, can also de-differentiate and acquire a myofibroblast/fibroblast phenotype [137]. Furthermore, cancer cells themselves "educate" ASCs through secreted factors and exosomes carrying specific miRNA and lncRNA, promoting their differentiation to CAF, reprogramming their cellular metabolism and influencing their migratory capability [139].…”
Section: The Adipose Tissue Stromal Stem Cellsmentioning
confidence: 99%
“…Abdominal obesity in particular is associated with an increased risk of aggressive prostate cancer [ 4 ]. The obese adipose environment is characterized by chronic inflammation driven in part by increased macrophage infiltration and elevated cytokine and adipokine expression [ 21 ]. This results in perturbed immune response and metabolic irregularities [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%